Protective or limited? Maternal antibodies and RSV-associated lower respiratory tract infection in hospitalized infants aged 28-90 days - Li, Shuanglian; Mei, Chenghao; Chen, Sainan; Wang, Chenglin; Gao, Yelei; Ma, Jinhua; Zhong, Li; Luo, Tingting; Zhao, Xin; Bu, Huaqin; Lyu, Ying; Kuang, Xiaohu; et al. (Frontiers in Immunology, 2025)
BackgroundRespiratory syncytial virus (RSV) is a major cause of severe health problems in newborns and young children. The protective role and limitations of serum maternal RSV antibodies in infants under 3 months remain controversial.MethodsA two-center prospective study from 2020 to 2023 recruited infants (n=286) admitted to the respiratory departments of two children’s hospitals in southwestern and southeastern China during RSV epidemic. These infants were hospitalized with lower respiratory tract infections (LRTI). We evaluated the relationship between serum RSV Prefusion (Pre-F), postfusion (Post-F) IgG levels, subtype neutralizing antibodies, and the incidence of RSV infection, as well as the relationship between these maternal antibodies and severity of disease. Since this prospective study only included data from RSV epidemic, we retrospectively reviewed medical records from the Children’s Hospital of Chongqing Medical University for the years 2019 to 2023 (n=3467) to analyze population characteristics during both RSV epidemic and non-epidemic periods, using the same inclusion and exclusion criteria.ResultThere were no significant differences in RSV Pre-F IgG, Post-F IgG, or RSV A or B neutralizing antibody levels between the RSV infected and non-infected groups during the epidemic. While RSV Pre-F IgG antibody was inversely correlated with disease severity, RSV Post-F IgG, and RSV A and B neutralizing antibodies did not show a similar correlation across the three illness severity categories. Additionally, there were no differences in age, gender, or illness severity distribution among hospitalized patients during epidemic and non-epidemic periods.ConclusionSerum maternal antibody levels offer insufficient protection against RSV-associated LRTI in hospitalized infants aged 28 to 90 days.